Variation in states’ implementation of CAPTA’s substance-exposed infants mandates: a policy diffusion analysis - Lloyd Sieger, Margaret H. (Child maltreatment, 2020)
In 2016, federal law changed state child welfare mandates related to prenatally substance-exposed infants. Little is known regarding the status or implications of policy implementation. The current study examined thematic clusters among states' policies responsive to this 2016 mandate. Cluster analysis identified four distinct categories of states' implementation: (1) "innovators/early adopters," (2) "early majority," (3) "late majority", and (4) "laggards". Innovator/early adopter states (n = 14) were most likely to have implemented plan of safe care policies consistent with Child Abuse Prevention and Treatment Act (CAPTA). Early majority states (n = 15) have started developing some aspects of CAPTA 2016 but have some aspects that are still in development. Late majority states (n = 17) have adopted few aspects of CAPTA 2016 but had implemented more CAPTA 2003 and 2010 aspects than states in the laggard cluster. Laggard states (n = 6) have implemented the fewest CAPTA prenatal substance exposure domains. In bivariate analyses, the only variable associated with clusters was Census region (e.g., New England), suggesting that states' implementation decisions may be influenced by their regional neighbors.